Enhancing efficiency of a laboratory-scale hybrid cooling tower using Fe3O4-water nanofluid and spiral coils - Danial Fallah Heravi; Hamid Reza Goshayeshi; Reza Saleh (Heliyon)
This study presents an in-depth investigation into improving the efficiency of a laboratory scale hybrid cooling tower by utilizing Fe₃O₄-water nanofluid at varying mass fractions, ranging from 0.015 % to 0.15 %, along with different coaxial spiral coil configurations. The experimental setup includes three spiral coils with diameters of 15 cm, 25 cm, and 35 cm, and a pipe diameter of 14 mm. By analyzing the relationship between cooling tower efficiency and the Merkel number, this research establishes a quantitative correlation between these factors. The novelty of this study lies in its unique combination of Fe₃O₄-water nanofluid and the spiral coil geometries, a configuration that has not been explored in prior studies for enhancing heat transfer in hybrid cooling towers.Experimental results indicate a significant 50 % improvement in cooling tower efficiency when Fe₃O₄-water nanofluid is used compared to pure water, largely due to enhanced thermal conductivity. Furthermore, the secondary flow generated by the spiral coils contributed an additional 8 % improvement in heat transfer. This work not only introduces a novel cooling tower design but also demonstrates the potential of nanofluids to significantly boost cooling efficiency in various industrial applications.By optimizing heat transfer performance through advanced fluid and geometric configurations, this study provides a comprehensive framework for future innovations in energy-efficient cooling technologies.Looking ahead, the research offers promising avenues for further exploration, such as optimizing nanofluid compositions, testing different nanomaterials or hybrid fluids, and exploring alternative tower configurations. The scalability of the proposed system presents strong potential for real-world industrial applications, driving the development of sustainable, energy-efficient cooling solutions in various sectors.